Paracoccidioidomicose : perfil epidemiológico, clínico e terapêutico dos pacientes diagnosticados nos serviços de referência do Estado de Mato Grosso (2006-2013) - Almeida, Hugo Luciano de (2014)
The paracoccidioidomycosis (PCM) is a systemic disease whose oral manifestations are quite common and often the first sign of the disease and, thus constituting fungal infection of great interest in dentistry. Data such as gender, age, occupation and origin of 230 patients seen in Public Laboratory of Mato Grosso and Julio Muller University Hospital (JMUH), about symptoms, anatomical location of the lesions, associated habits like smoking, drinking and illicit drug use, comorbidities, laboratory diagnosis, treatment instituted, the type of entry if new case, relapse or re-entry after abandonment, seasonality and closure of each case were collected. The results showed that the PCM is endemic in Mato Grosso being more frequent in North and Central South mesoregions of state and affecting mostly adult males who have or have had their work activities related to rural areas or that the nature of work are more exposed to inhalation of dust. Oral lesions were most frequently found. As therapeutic conduct to trimethoprim-sulfamethoxazole remains the most used drug due to the low cost and availability in the Unified Health System – SUS (the public health system in Brazil) in the state of Mato Grosso. There is high rate of abandonment and discontinuance of treatment of patients seen at JMUH. The rate of smoking and alcohol consumption associated with PCM was quite high. It was observed that most dentists do not feel able to diagnose PCM and they ignore the reference services.